ANALISIS FRAMING PEMBERITAAN ISU PEMULANGAN WNI EKS-ISIS DALAM PORTAL BERITA BBC NEWS INDONESIA - Widyastini Susila, Ni Putu Sri; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
The issue of repatriation of ex-ISIS Indonesian citizens have become controversial in Indonesia. This research conducted to find out how the issue was framed by BBC News Indonesia. This research uses a descriptive qualitative approach. The data source is obtained from the BBC's coverage series with the theme ‘Setelah ISIS Jatuh' which was published in February 2020. The method used in this research is Robert Entman's framing model analysis which states that every media constructing news must go through four stages, (1) define problems, (2) diagnose causes, (3) make moral judgment, and (4) treatment recommendation. The results, BBC News Indonesia admits that ISIS is a dangerous organization that threatens world security, so it is natural that ISIS militants are not given a pardon to return to their country of origin. However, the BBC highlights the lives of children who have fallen victim to ISIS to be pardoned for humanitarian reasons. Keyword : Indonesian citizens ex-ISIS, BBC News Indonesia, framing